Impact of Curriculum Implementation Support Programme in changing the Knowledge, Attitude and Perceptions of Medical faculties towards Competency Based Medical Education in a Private Medical College - Nagar, Noopur; Shashwat Nagar; Jankhwala, Mohmed Soeb; Patel, Reekee; Shukla, Aparajita; Godara, Naresh (Indian Journal of Community Health, 2024)
Background: CBME is a skill-based curriculum focusing on the desired competencies stated to be achieved by merits. To sensitize and train the faculty about CBME, the Curriculum Implementation Support Program (CISP) workshops have been held at various colleges across India. Aim& Objective: To find out the changes in the knowledge, perceptions and attitudes among medical teachers regarding CBME following CISP training. Methods and Material: The study carried out was cross-sectional and the data was collected before and after conduction of the CISP training programme. All the medical teachers who were enrolled in the CISP training were included in the study. The outcome result for knowledge-based questions was recorded as multiple choice options and that for attitudes and perceptions was recorded with a 5-point Likert scale ranging from strongly agree to strongly disagree. Statistical analysis used: Descriptive statistics were calculated using numbers and simple proportions. Results: There was a significant improvement in the knowledge and perceptions of medical teachers following CISP training showing its impact. The perceived challenges as felt by the faculties also reduced substantially. Conclusions: Capacity building programmes must be conducted at regular intervals for faculties for successful implementation of all the components of CBME.